2021
DOI: 10.3390/cancers13112526
|View full text |Cite
|
Sign up to set email alerts
|

Nature-Inspired Nanoparticles as Paclitaxel Targeted Carrier for the Treatment of HER2-Positive Breast Cancer

Abstract: Despite the advances made in the fight against HER2-positive breast cancer, the need for less toxic therapies and strategies that avoid the apparition of resistances is indisputable. For this reason, a targeted nanovehicle for paclitaxel and trastuzumab, used in the first-line treatment of this subtype of breast cancer, had already been developed in a previous study. It yielded good results in vitro but, with the aim of further reducing paclitaxel effective dose and its side effects, a novel drug delivery syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…PDA NPs, despite not being loaded with taxane or anti-HER2 antibody, have shown remarkable antitumor activity in vitro in HER2+ conventional cell cultures and breast tumor spheroids. 179 Encapsulation of diosgenin in PLGA nanoparticles, coated with folic acid-chitosan, yielded a stable formulation with potent anticancer effects against TUBO breast cancer cells. In vitro and in vivo studies demonstrated dose-dependent inhibition of tumor growth and apoptosis induction.…”
Section: Targeting Potential Of Nanoformulations For Breast Cancer Tr...mentioning
confidence: 99%
“…PDA NPs, despite not being loaded with taxane or anti-HER2 antibody, have shown remarkable antitumor activity in vitro in HER2+ conventional cell cultures and breast tumor spheroids. 179 Encapsulation of diosgenin in PLGA nanoparticles, coated with folic acid-chitosan, yielded a stable formulation with potent anticancer effects against TUBO breast cancer cells. In vitro and in vivo studies demonstrated dose-dependent inhibition of tumor growth and apoptosis induction.…”
Section: Targeting Potential Of Nanoformulations For Breast Cancer Tr...mentioning
confidence: 99%
“…Moreover, drug-loaded HA nanoparticles specifically bind to CD44 receptors, which are highly expressed on activated HSCs, thereby enhancing the antitumor effect via CD44 receptor-mediated endocytosis (28,29). The use of drug-loaded HA nanoparticles has been demonstrated in cancer treatment, such as that of breast cancer, HCC and colorectal cancer (30)(31)(32).…”
Section: A Ph-responsive Hyaluronic Acid Nano-vehicle Co-encapsulatin...mentioning
confidence: 99%
“…Similar conclusions were drawn following the testing on 3D cultured cells, where it was shown that PDA-NPs disintegrated and reduced the viability of HER2+ breast tumor spheroids. Furthermore, the authors showed that the charged PDA-NPs reduced the viability of stromal cells to a lesser extent compared to similar concentrations of PTX [ 100 ].…”
Section: Melanin-based Targeted Cancer Therapymentioning
confidence: 99%